PENDIDIKAN KEWARGANEGARAAN MULTIKULTURAL SEBAGAI WAHANA PENDIDIKAN HUKUM DAN KESADARAN BERKONSTITUSI - Zuriah, Nurul (Sekolah Tinggi Hukum Bandung, 2010)
Multicultural Citizenship Education in the college environment is one of the strategic and fundamental instrument in the frame of national education. Civics assumed an important role as a vehicle for character education and transformation, desimenation nation and character building which has the legal awareness and high constitution, in the middle of heterogeneity, pluralism and multiculturalism which became the main characteristic of the Indonesian nation. Strategic role of civic education is expected to foster nationalism and the dynasty of high ideals in college students. This is based out of a sense of nationalism and aspirations can be achieved dynasty taken for granted or trial and error, on the contrary should be sought in a systematic, programmatic, integrated, sustainable.Keywords: Multicultural Citizenship Education - Nation and Character BuildingÂ - Legal Awareness